2019
DOI: 10.1101/792416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Physiological synchrony promotes cooperative success in real-life interactions

Abstract: 15interaction. 20 Significance StatementHuman cooperation is remarkable in its scale, complexity, and efficiency. However, whereas people think of themselves as rational agents, they actually partly base their decision to cooperate with someone on gut feelings. These feelings are informed by non-verbal expressions that are picked up implicitly and that synchronize across interaction partners. For the first time, 5 we show that the alignment of people's arousal over multiple rounds of the Prisoners' dilem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…(2) there were differences between the two conditions, but the method was not sensitive to detect them. In support of the first explanation, in two previous studies, we have used parameters included in the current analysis with which we were able to detect differences in within-subject conditions and could link it to interpersonal outcomes (Behrens et al, 2019;Prochazkova, Sjak-Shie, Behrens, Lindh, & Kret, 2019). The method therefore has been shown to be sensitive in other contexts.…”
Section: Change In Synchronymentioning
confidence: 77%
See 3 more Smart Citations
“…(2) there were differences between the two conditions, but the method was not sensitive to detect them. In support of the first explanation, in two previous studies, we have used parameters included in the current analysis with which we were able to detect differences in within-subject conditions and could link it to interpersonal outcomes (Behrens et al, 2019;Prochazkova, Sjak-Shie, Behrens, Lindh, & Kret, 2019). The method therefore has been shown to be sensitive in other contexts.…”
Section: Change In Synchronymentioning
confidence: 77%
“…To study the underlying mechanisms of synchrony, its boundary conditions and individual differences, researchers are often interested in how synchrony changes in relation to experimental manipulations. For example, in a previous study, we observed that physiological synchrony promoted cooperative success, but only when partners could see each other and not when a cover prevented eye contact (our manipulation) (Behrens et al, 2019). Another study investigated the effect of emotional salience during storytelling on pupil mimicry and showed that physiological coupling between the speaker and the listener was stronger during emotionally intense moments compared to less salient moments (Kang & Wheatley, 2017).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The MEA software tool utilizes pixel differencing methods to quantify motion in selected regions of a video stream. MEA has been used in a number of behavioral studies with topics ranging from patients and care-provider interactions in psychotherapy sessions and medical settings, to team-based cooperative problem solving (e.g., Behrens et al, 2019;Hamel et al, 2018;Nelson, Grahe, Ramseyer, & Serier, 2014). Recently, Daniel et al (2020) used ecological momentary assessment (EMA) methodologies to model the effect of cognitive bias modification strategies on the behaviors of individuals high in social anxiety.…”
mentioning
confidence: 99%